Fournier gangrene - Niiyasu, Shoya (Journal of the Japan Organization of Clinical Dermatologists, 2025)
Fournier gangrene (FG) is defined as necrotizing fasciitis that progresses rapidly, mainly in the genital, perineum, and perianal areas, and has a high mortality rate. Therefore, it is important to immediately assess the disease severity and initiate appropriate treatment. We report a case of FG in which indices, such as the Uludag FG severity index (UFGSI) and simplified FGSI (SFGSI), were low. Appropriate treatment was administered, and the patient did not develop severe disease.The patient was a 59-year-old man who has been suffering from buttock pain for eight days. Oral antibiotic treatment was initiated at a local hospital; however, there was no improvement. He had difficulty walking; therefore, he was referred to our department. Erythema and fluctuating motions were observed on the right scrotum and left buttock, and a snow-grabbing sensation was palpable in the right scrotum. Contrast-enhanced computed tomography revealed gas and liquid accumulation with a clear border around the perineum; hence, FG was diagnosed. The LRINEC score was 8, and necrotizing fasciitis was considered; however, the UFGSI was 7 and SFGSI was 0, indicating a low-risk assessment. Streptococcus constellatus and Prevotella bivia were detected in the necrotic tissue cultures. Incision, drainage, and debridement were performed, and the affected area and overall condition rapidly improved.FGSI and UFGSI are useful for assessing the risk of FG. As these scores are difficult to calculate, a simplified version of the SFGSI has been devised and reported to be a useful index. Early diagnosis and treatment of FG are extremely important. We believe that indices that predict disease progression, such as the UFGSI and SFGSI, are useful.